O PARAÍSO KEY WEST - UMA VISÃO DE SEGMENTAÇÃO DE MERCADO - Myriam de Andrade Caminha Costa (Universidade do Oeste Paulista, 2007)
Society each time more, needs mechanisms to surpass problems and limitations. One understands that the world-wide tourism if characterizes for possessing great capacity of adaptation and segmentation of markets, on the basis of the dynamic of estruturação of new products and also in new consuming markets. The Tourism constitutes a economic activity that promotes one of the biggest factors of development. Key West it is the last Florida island Keys - joint of islands to the south of the Flowery one - Been Joined. The natural beauty of these islands forms a great tourist polar region. Key West had its economy shaken for the weakness of the commerce of the cigar, the sponges and the withdrawal of the Armed Forces; the tourism redirected its economy. Tourism Single it is a segmentation of market of the tourism that encloses some interfaces, such as: ecological tourism, of adventure, GLBT, cultural, among others. Key West for its ample gamma of performance, can be seen as a lesson of integration between cultures, social tolerance, ambient conscience and sustentabilidade.